2012
DOI: 10.1111/wbm.12004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term fertilization on the weed growth and community composition in a double‐rice ecosystem during the fallow period

Abstract: The vegetation cover during the non‐cropping season could have important implications for the maintenance and recovery of soil fertility, as well as for biodiversity conservation in croplands. In this study, five fertilization regimes (control: non‐fertilization; N: inorganic N fertilization; P: inorganic P fertilization; NPK: balanced fertilization with inorganic N, P and K; NPKM: balanced NPK plus farmyard manure) were conducted from 1981 in a double‐rice (Oryza sativa L.)‐cropping system in subtropical Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 41 publications
(96 reference statements)
0
6
0
Order By: Relevance
“…3, Appendix S4). Decreases in soil K content and increases in soil N:K ratios are associated with a loss of species richness (Huang et al, 2013). Moreover, P:K soil ratios can increase because the solubility and mobility of K are higher than those of P; therefore K is more easily leached than P (Olde Venterink et al, 2009).…”
Section: Potassium Stoichiometry and Global Changementioning
confidence: 99%
“…3, Appendix S4). Decreases in soil K content and increases in soil N:K ratios are associated with a loss of species richness (Huang et al, 2013). Moreover, P:K soil ratios can increase because the solubility and mobility of K are higher than those of P; therefore K is more easily leached than P (Olde Venterink et al, 2009).…”
Section: Potassium Stoichiometry and Global Changementioning
confidence: 99%
“…Several studies have reported that fertilization has a strong impact on weed species' abundance and diversity (Banks et al, 1976;Nie et al, 2009;Cheimona et al, 2016). In particular, quite a few experiments have demonstrated that high level of nitrogen (N) fertilization results in decrease of weed species richness (Pyšek and Lepš, 1991;Inouye and Tilman, 1995) and change of the weed species composition, since specific species are favored (Mahn, 1988;Gu et al, 2007;Huang et al, 2013). Moreover, Storkey et al (2010) found that several rare and endangered weed species were further reduced due to the added nitrogen.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been shown that the variability of physical properties is lower compared to chemical properties, mainly because they respond to macrogeographic conditions such as climate, topography and geological parent material (Novillo et al, 2018;Awal et al, 2019). Recently, it has been evidenced that physicochemical variation responds mainly to intrinsic and anthropogenic factors of the crop, even to a greater extent than in relation to environmental conditions (Huang et al, 2013;Little et al, 2015).…”
Section: Resultsmentioning
confidence: 99%